PERENCANAAN SISTEM DRAINASE BERWAWASAN LINGKUNGAN JALAN TOL GEMPOL PAKET I - Farid Rahadian, Agus Suhardono, Mohammad Zenurianto (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2015)
The 5,500 m Gempol Toll Road Package I needs an environment-oriented drainage system design completed with infiltration well made at an interval of 100 m of rainwater function and maintain ground water level.The design needs some data of situational map, long-section, and rainfall from 3 nearby stations: Gempol, Winong, and Bareng, in 2002-2012. The rainfall data were processed to analyze the maximum rainfall rate; Mean Algebra Method was employed for local rainfall calculation, and Log Pearson type III was used for the 10-year design rainfall which results in 121.281 mm.The calculations result in 0,023 m³/dt rain water discharge flow to the river; rainwater tank dimensions of 2.25 m2 in area and 3 m in depth; 54 tanks on the left and 55 tanks on the right; and two 0.6 m Æ pre-cast culvert rings. The rectangular drainage channels were of stone river with dimensions of 0.7 m in width and 0.6 m in depth. The project takes 204 workdays at IDR Rp 9.633.074.000 cost.Keywords: drainage system; infiltration well; design flood.